If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -54 + -10x = 10x + 16 Reorder the terms: -54 + -10x = 16 + 10x Solving -54 + -10x = 16 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -54 + -10x + -10x = 16 + 10x + -10x Combine like terms: -10x + -10x = -20x -54 + -20x = 16 + 10x + -10x Combine like terms: 10x + -10x = 0 -54 + -20x = 16 + 0 -54 + -20x = 16 Add '54' to each side of the equation. -54 + 54 + -20x = 16 + 54 Combine like terms: -54 + 54 = 0 0 + -20x = 16 + 54 -20x = 16 + 54 Combine like terms: 16 + 54 = 70 -20x = 70 Divide each side by '-20'. x = -3.5 Simplifying x = -3.5
| 2(-3)-5y=13 | | 9k+ar=r-2y | | 32=-4(3p+7) | | -1=-5x | | 2(-3)5y=13 | | 3-(2x-5)=7 | | 2(5m-6)=28 | | p-3q=10 | | 3(2a+1)-4=11 | | 9v^2=-30v-25 | | 6x-5x=+1 | | 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 | | 20=4(d+3) | | (7+2a)+3a= | | 2-5y=13 | | 4(-3)+6(-8)+(-3)(78)-7(-42)= | | 6+x-x^2=0 | | n-12=5n+4 |